2021
DOI: 10.3390/rs13224529
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Sentinel-2, MODIS, CGLS, SAF, GLASS and C3S Leaf Area Index Products in Maize Crops

Abstract: We proposed a direct approach to validate hectometric and kilometric resolution leaf area index (LAI) products that involved the scaling up of field-measured LAI via the validation and recalibration of the decametric Sentinel-2 LAI product. We applied it over a test study area of maize crops in northern China using continuous field measurements of LAINet along the year 2019. Sentinel-2 LAI showed an overall accuracy of 0.67 in terms of Root Mean Square Error (RMSE) and it was used, after recalibration, as a be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…At the satellite level, the parametric method proved to be effective even when compared against Sentinel-2 Biophysical Processor LAI estimations, which are often used due to their independence from specific information regarding the field conditions and crop types (Levitan et al, 2019). The comparison between the ground-measured LAI and parametric Sentinel-2 and UAV LAI estimations showed clear underestimations in the Sentinel-2 LAI MLA -generated product, as was also pointed out by Djamai et al (2019) for a variety of crops and by Xie et al (2019) for winter wheat; however, this result contrasted with that reported by (Yu et al, 2021) for maize, where the Sentinel-2 LAI MLA product resulted in fairly good estimations. Nonetheless, the MLA method was able to retrieve relative LAI reductions between undamaged and damaged vegetation consistently with those found through the parametric estimation.…”
Section: Discussionmentioning
confidence: 73%
“…At the satellite level, the parametric method proved to be effective even when compared against Sentinel-2 Biophysical Processor LAI estimations, which are often used due to their independence from specific information regarding the field conditions and crop types (Levitan et al, 2019). The comparison between the ground-measured LAI and parametric Sentinel-2 and UAV LAI estimations showed clear underestimations in the Sentinel-2 LAI MLA -generated product, as was also pointed out by Djamai et al (2019) for a variety of crops and by Xie et al (2019) for winter wheat; however, this result contrasted with that reported by (Yu et al, 2021) for maize, where the Sentinel-2 LAI MLA product resulted in fairly good estimations. Nonetheless, the MLA method was able to retrieve relative LAI reductions between undamaged and damaged vegetation consistently with those found through the parametric estimation.…”
Section: Discussionmentioning
confidence: 73%